Gry jako moralne laboratorium. Gamifikacja dylematów moralnych bezzałogowych samochodów - Maćkiewicz, Bartosz; Mamak, Wojciech (Replay. The Polish Journal of Game Studies, 2018)
The aim of this paper is to identify potential dangers and benefits of investigating moral intuitions about the autonomous vehicles (AVs), using gamified research tools. We argue that computer games facilitate constructing more ecologically valid experiments. Due to the increased validity, the experimental outcomes can represent the real-life mechanisms of decision-making more faithfully. Data extracted in this manner could be used in implementation of ‘moral modules’ in AVs built in the real world. In our paper we analyze selected experimental setups that use game-like elements and assess them in the light of current literature regarding the algorithmization of ethics and implementability of ethical frameworks in machines. We also show how this problem can be interpreted in an overarching conceptual scheme of Floridi’s ‘information ethics’.